The innate immune response to non-infectious stressors : human and animal models - Amadori, Massimo (Academic Press is an imprint of Elsevier, 2016)
The Innate Immune Response to Non-infectious Stressors: Human and Animal Models highlights fundamental mechanisms of stress response and important findings on how the immune system is affected, and in turn affects such a response. In addition, this book covers the crucial link between stress response and energy metabolism, prompts a re-appraisal of some crucial issues, and helps to define research priorities in this fascinating, somehow elusive field of investigation.